Gene expression analysis of subchondral bone, cartilage, and synovium in naturally occurring equine palmar/plantar osteochondral disease. Issue 3 (16th May 2021) - Turlo, Agnieszka J.; McDermott, Benjamin T.; Barr, Elizabeth D.; Riggs, Chris M.; Boyde, Alan; Pinchbeck, Gina L.; Clegg, Peter D.
Abstract: Osteoarthritis (OA) is a disease of the entire joint but the relationship between pathological events in various joint tissues is poorly understood. We examined concurrent changes in bone, cartilage, and synovium in a naturally occurring equine model of joint degeneration. Joints ( n = 64) were grossly assessed for palmar/plantar osteochondral disease (POD) in racehorses that required euthanasia for unrelated reasons and assigned a grade of 0 ( n = 34), 1 ( n = 17), 2 or 3 ( n = 13) using a recognized grading scheme. Synovium, cartilage, and subchondral bone were collected for histological and gene expression analysis. Relations between POD grade, cartilage histological score, and gene expression levels were examined using one‐way analysis of variance or Kruskal–Wallis test and Spearman's correlation coefficient with corrections for multiple comparisons. Cartilage histological score increased in joints with POD grade 1 ( p = 0.002) and 2 or 3 ( p < 0.001) compared to 0. At grade 1, expression of COL1A1, COL2A1, and MMP1 increased and BGN decreased in subchondral bone while expression of BGN and ACAN decreased in cartilage. These changes further progressed at grades 2 and 3. POD grades 2 and 3 were associated with decreased expression of osteoclast inhibitor OPG and increased markers of cartilage degeneration (MMP13, COL1A1). Expression of the vascular endothelial growth factor decreased with POD grade and negatively correlated with cartilage histological score. Synovium showed no histological or transcriptomic changes related to pathology grade. Cartilage degeneration in POD is likely to be secondary to remodeling of the subchondral bone. Limited activation of proinflammatory and catabolic genes and moderate synovial pathology suggests distinct molecular phenotype of POD compared with OA.